Pengembangan Handout Pada Materi Listrik Dinamis Berbasis Science Environment Technology and Social - deswita, pipi; wulan, ratna; usmeldi, usmeldi (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The background of this research is student understanding about naturalÂ  phenomena is quite low. Students curiousity about dinamic electricity and its relation with environment and technology, and its utilization in our daily life has not developed. One of the approximation to reach the purpose is Science Environment Technology And Social (SETS) approximation. This research purpose is to develop a valid, practice an effective high school physics learning equipments based on SETS especially on dynamic electricity. McKenny model is used as development model, consist of preliminary, prototyping stage, and assesment stage. The research showed that the handout for high school physics based on SETS can be categorized as valid, very practis, and very effective so it can be implemented on the learning process.